2010
DOI: 10.1161/circimaging.109.890848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Loading Condition on the 2D Speckle Tracking–Derived Left Ventricular Dyssynchrony Index in Nonischemic Dilated Cardiomyopathy

Abstract: Background-The effects of left ventricular (LV) loading conditions on LV dyssynchrony have not been elucidated. We modified LV loading conditions to reveal their effects on echocardiography-derived LV dyssynchrony index (LVdys) in patients with documented nonischemic dilated cardiomyopathy. Methods and Results-Thirty-seven patients were consecutively enrolled. After baseline measurements, pneumatic compression of the lower extremities (Pcom) was used to increase LV afterload. Subsequently, sublingual nitroglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 42 publications
4
19
0
Order By: Relevance
“…A U G U S T 1 1 , 2 0 1 5 : 6 3 1 -4 1 changes in regional loading conditions, may manifest time-to-peak differences that are not due to a true electrical activation delay (31). In the present study, dyssynchrony by time-to-peak indexes was significantly associated with outcome, with HRs similar to those previously reported (19) STUDY LIMITATIONS.…”
Section: Lbbb Contraction Patterns and Long-term Crt Outcomesupporting
confidence: 84%
“…A U G U S T 1 1 , 2 0 1 5 : 6 3 1 -4 1 changes in regional loading conditions, may manifest time-to-peak differences that are not due to a true electrical activation delay (31). In the present study, dyssynchrony by time-to-peak indexes was significantly associated with outcome, with HRs similar to those previously reported (19) STUDY LIMITATIONS.…”
Section: Lbbb Contraction Patterns and Long-term Crt Outcomesupporting
confidence: 84%
“…Studies on CRT have demonstrated that LV systolic dysfunction is related to increased radial dyssynchrony18, 19. Additionally, changes in loading conditions can result in significant LV dyssynchrony28. Similarly, the slight LV dyssynchrony observed in this study after attenuation of PDA flow was a reflection of transient myocardial dysfunction caused bydecreased preload.…”
Section: Discussionsupporting
confidence: 53%
“…39 The ability of strain imaging to quantify the regional timing of deformation has led to its widespread application in the assessment of ventricular synchrony. Quantifying the temporal dispersion in contractility has provided important insights into the load dependency of ventricular dyssynchrony, 40 the linkage between dyssynchrony and impaired contractile function, 41 and the prognostic relevance of dyssynchrony in select groups of patients with QRS duration Ͻ120 ms. 42 These measures have also been used to assess the relationship between dyssynchrony measures and response after resynchronization therapy. Using both the magnitude and timing of regional deformation, Delgado et al 43 demonstrated the importance of both lead positioning and contractile function, as they relate to the most delayed myocardial segment, in predicting response to cardiac resynchronization therapy.…”
Section: Quantification Of Regional Functionmentioning
confidence: 99%